Faktor-Faktor Yang Mempengaruhi Minat Mahasiswa Untuk Mengikuti Program Relawan Pajak - Sayyidah Salsabila; Achmad Wicaksono (LPPM Universitas Putera Batam, 2026)
The tax volunteer program is a collaborative effort between the directorate general of taxes and higher education institutions designed to enhance public understanding and awareness of taxation through student participation. Nevertheless, students’ involvement in this program does not occur automatically and is shaped by various influencing factors. This study seeks to identify the factors that influence students’ interest in joining the Tax Volunteer Program and to explore how students interpret the experiences gained from their participation. A qualitative approach employing a descriptive exploratory method was applied, with data collected through in-depth interviews involving students who had served as tax volunteers. The results indicate that students’ interest is influenced by a combination of academic, social, and internal motivational factors, including alignment between the program and their academic discipline, support from the campus environment, and the motivation to improve tax knowledge and professional skills. Furthermore, direct engagement in assisting taxpayers contributes to the development of professional attitudes, enhanced communication abilities, and more favorable perceptions of the taxation field. This study concludes that the Tax Volunteer Program functions not only as a tool for public tax education but also as an experiential learning platform that fosters students’ interest, competencies, and career orientation in taxation.